2003
DOI: 10.1063/1.1556555
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile electrical bistability of organic/metal-nanocluster/organic system

Abstract: Two-terminal electrical bistable devices have been fabricated using a sandwich structure of organic/ metal/organic as the active medium, sandwiched between two external electrodes. The nonvolatile electrical bistability of these devices can be controlled using a positive and a negative electrical bias alternatively. A forward bias may switch the device to a high-conductance state, while a reverse bias is required to restore it to a low-conductance state. In this letter, a model to explain this electrical bista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
268
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 353 publications
(276 citation statements)
references
References 9 publications
4
268
4
Order By: Relevance
“…9 Semiconducting materials, for example, MoO 3 and so on, 10 with suitable energy band levels can also be used in place of the metal particles. However, as shown by the vast differences in the electrical characteristics of the devices fabricated in different laboratories, 3,[6][7][8] the reproducibility of the device depends very much on the vacuum chamber and deposition conditions. Therefore, a more repeatable fabrication process is required for the large-scale manufacture of such devices.…”
Section: Device Structure and Fabrication Of The Nonvolatile Memory Dmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Semiconducting materials, for example, MoO 3 and so on, 10 with suitable energy band levels can also be used in place of the metal particles. However, as shown by the vast differences in the electrical characteristics of the devices fabricated in different laboratories, 3,[6][7][8] the reproducibility of the device depends very much on the vacuum chamber and deposition conditions. Therefore, a more repeatable fabrication process is required for the large-scale manufacture of such devices.…”
Section: Device Structure and Fabrication Of The Nonvolatile Memory Dmentioning
confidence: 99%
“…The metal layer has been shown not to form a continuous film when the deposition rate and the thickness are low (Figure 1). [6][7][8] For the case of aluminum, aluminum oxide may be formed spontaneously because of residual oxygen in the vacuum chamber. 6 This insulating oxide layer is believed to be important as it can improve the charge retention properties of the nanoparticles.…”
Section: Device Structure and Fabrication Of The Nonvolatile Memory Dmentioning
confidence: 99%
See 1 more Smart Citation
“…One emerging candidate is the resistance random access memory (RRAM) based on metal oxides [2,3] and organic semiconductors [4][5][6]. These RRAMs have shown electrically induced resistive switching effects and have been proposed as the basis for future non-volatile memories.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous paper it has shown that the resistive switching will occur through the polymer capped nanostructure silver oxide embedded in a planer diode with two gold electrodes [1]. There are lots of reports showing different mechanisms for resistive switching observation [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%